Single‐Step Synthesis of Dehydroalanine Derivatives via a Brønsted Acid‐Catalyzed Multicomponent Reaction. Issue 11 (17th March 2020) - Bartoccini, Francesca; Mari, Michele; Retini, Michele; Galarini, Roberta; Bartolucci, Silvia; Piersanti, Giovanni
Abstract: A single‐step practical synthesis of dehydroalanine (Dha) derivatives from commercially available starting materials is reported. The approach comprises a Brønsted acid‐catalyzed three‐component condensation reaction of pyruvic acid, an alcohol/thiol, and an amide/carbamate. This protocol provided access to several Dha derivatives, including a novel chiral version modified with diverse functional groups, which might be useful for further transformations in the construction of more complex molecules. Abstract : Single‐step Synthesis of Dehydroalanine Derivatives via a Brønsted Acid‐Catalyzed Multicomponent Reaction. A single‐step synthesis of dehydroalanine (Dha) derivatives has been achieved through a Brønsted acid‐catalyzed three‐component condensation reaction of pyruvic acid, an alcohol/thiol, and an amide/carbamate.